The middle class in Emerging Asia Champions for more inclusive societies? - Bonnet, Antoine (OECD Development Centre Working Papers, 2021)
As Asian societies continue to undergo rapid economic transformation, income distribution and social stratification are set to change radically. A primary characteristic of this evolution is the emergence of wealthier Asian middle-income classes. While middle-income classes are a heterogeneous group, they often come with new policy expectations, and the extent to which they will call for policy changes that are beneficial to more fragile segments of society remains unclear. This paper investigates the characteristics of different income classes in Asia in order to explore the extent to which the emergence of wealthier Asian middle-income classes could become a driver for more inclusive societies. From this perspective, we assess whether middle-income classes share common characteristics with the poor and the near-poor in six Asian countries, i.e. Cambodia, China, Indonesia, Thailand, Pakistan and Viet Nam. The paper finds that, in some aspects, middle-income classes share a number of similar characteristics with lower income classes. We discuss how this resemblance could result in support for policies that could benefit larger segments of society. We also underline the necessity to better integrate the needs of the poor and the near-poor in policy discussions, especially in areas where the interests of lower and upper income classes do not necessarily converge